Electrochemical Milling of TB6 Titanium Alloy in NaNO3 Solution. Issue 2 (31st January 2019) - Liu, Yang; Qu, Ningsong
Abstract : Owing to its high tensile strength and toughness, TB6 titanium alloy has been widely used in aerospace applications. However, the machining of TB6 titanium alloy via traditional processes is inefficient as a result of significant tool wear and the prolonged machining cycle. Electrochemical machining is suitable for processing TB6 titanium alloy as it does not cause tool wear or thermal deformation. However, few researchers have conducted an in-depth study of the electrolytic processing of TB6 titanium alloy with the widely used NaNO3 solution. Some researchers have even suggested that TB6 titanium alloy cannot be processed by electrolysis in NaNO3 solution. This paper focuses on the electrochemical machining of TB6 titanium alloy in NaNO3 solution. To explore the effect of the electrochemical parameters on the dissolving behavior of TB6, anodic polarization curves were analyzed. The experimental results show that efficient electrochemical dissolution can be obtained in 20% NaNO3 solution. In addition, the effects of different current densities and processing times on the surface composition and morphology of TB6 titanium alloy were investigated. An electrochemical dissolution characteristic model was proposed to illustrate the dissolution process of TB6 titanium alloy. Finally, grooves and flat surfaces were produced successfully by electrochemical milling.